Using SpaceClaim scripts to create training models - V. V. Naprasnikov; Zirui Wang; I. L. Kovaleva; S. N. Novikov (Системный анализ и прикладная информатика)
One of the possible approaches in the formation of the geometric part of the finite-element model in the process of teaching students is the use of the language IronPython in SpaceClaim environment with the purpose of subsequent modeling on the platform ANSYS WorkBench. The comparative advantages of Design Modeler and SpaceClaim for such a problem are described. An example of using this approach in a real learning process is given.